Customer Analysis Review, Product Quality and Promotion on Purchasing Decisions for Cosmetic Products in E- commerce Shopee - Serin Anasya; Siska Fidia Lestari; Ramlah Puji Astuti (Cita Konsultindo Research Center, 2024)
This research aims to determine the influence of customer reviews, product quality and promotions on purchasing decisions for cosmetic products on Shopee e-commerce. The population used in this research is Shopee consumers who have purchased cosmetic products. The sample selection technique in this study used non-probability sampling with the purposive sampling method. This research uses Naresh K Malhotra's theoretical formula with a total of 88 respondents. The analytical methods used include validity and reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis and hypothesis tests (F test and T test). Analysis of the data used can see that the independent variable has an influence on the dependent variable. The research results show that customer reviews (X1) have a significant positive effect on purchasing decisions, product quality (X2) have a significant positive effect on purchasing decisions, and promotions (X3) have a significant positive effect on purchasing decisions. Customer reviews, product quality and promotions simultaneously influence decisions to purchase cosmetic products on Shopee e-commerce.